2022
DOI: 10.3389/fmed.2022.873538
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Molecular Compounds as Potential Indicators for Meibomian Gland Dysfunction

Abstract: Meibomian gland dysfunction (MGD) is the leading cause of dry eye disease throughout the world. Studies have shown that several molecules in meibum, including but not limited to interleukins, amino acids, cadherins, eicosanoids, carbohydrates, and proteins, are altered in meibomian gland dysfunction compared with healthy normal controls. Some of these molecules such as antileukoproteinase, phospholipase A2, and lactoperoxidase also show differences in concentrations in tears between meibomian gland dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Previous studies on meibum proteomics revealed that meibomian glands secrete a number of proteins into the tear film and more than 90 proteins have been identified in human meibum involving keratins (K1, 5, 6, 7, 9, 10, 13, and 16), surfactant proteins (SP-B and SP-C), lipocalins, lactoferrin, phospholipid transfer proteins, lipophillins, cytochrome c, farnesoid X laminin α-3 chain, lysozyme c, and proteoglycans. 60 62 It is intriguing here that, overall, the lipids were reduced in short glands, but the protein concentration was higher. How proteins interact with lipids and their association with gland morphology needs to be explored further.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies on meibum proteomics revealed that meibomian glands secrete a number of proteins into the tear film and more than 90 proteins have been identified in human meibum involving keratins (K1, 5, 6, 7, 9, 10, 13, and 16), surfactant proteins (SP-B and SP-C), lipocalins, lactoferrin, phospholipid transfer proteins, lipophillins, cytochrome c, farnesoid X laminin α-3 chain, lysozyme c, and proteoglycans. 60 62 It is intriguing here that, overall, the lipids were reduced in short glands, but the protein concentration was higher. How proteins interact with lipids and their association with gland morphology needs to be explored further.…”
Section: Discussionmentioning
confidence: 84%
“…At the same time, unique protein species in SS sampling may indicate biochemical changes associated with reflex tearing. While contaminants such as keratins can be introduced during sample prep, they are also an important component of meibum [ 35 ] and are expected to be present in tears, given the proximity of host ocular adnexal skin. Thus, keratins should be considered a natural component of tears.…”
Section: Discussionmentioning
confidence: 99%